Biological control of maize downy mildew with the antagonistic bacterial consortium - ENDANG MUGIASTUTI; ABDUL MANAN; LOEKAS SOESANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Mugiastuti E, Manan A, Soesanto L. 2023. Biological control of maize downy mildew with the antagonistic bacterial consortium. Biodiversitas 24: 4644-4650. Downy mildew is one of the main diseases of maize, which is a limiting factor for maize production in Indonesia. With a consortium of maize-indigenous antagonist bacteria, biological control is expected to reduce downy mildew. The aim of this research was to determine the ability of three antagonistic bacteria Bacillus amyloliquefaciens BB.R3, Bacillus subtilis BB.B4, Pseudomonas putida BB.R1 in suppressing spore germination of Peronoslerospora spp., and to evaluate the ability of their consortium in controlling downy mildew and promote the growth of maize. Based on the research results, antagonistic bacteria B. amyloliquefaciens BB.R3, B. subtilis BB.B4, and P. putida BB.R1 were able to suppress spore germination by 76.68-100%. The bacterial consortium of Bacillus subtilis BB. B4 + Pseudomonas putida BB.R1 was the best consortium of antagonistic bacteria and had the most potential to developed as a downy mildew control and promote the growth of maize. This bacterial consortium delayed the incubation period, lowered the intensity of the disease (85.77%) and AUDPC (83.02%), increased the content of phenols (tannins, glycosides, and saponins), and promoted plant growth (plant height 138.10%, the number of leaves 102.29%, root length 219.89%, fresh plant weight 1091.81%, and dry plant weight 1077.04%) compared to the control. Treatment with antagonistic bacteria showed better results compared to the fungicide metalaxyl. Based on the results, applying antagonistic bacteria consortium is a potential strategy to control maize downy mildew.